Maternal effects alter the severity of inbreeding depression in the offspring - Pilakouta, Natalie; Smiseth, Per T. (Proceedings of the Royal Society. B, Biological sciences, 2016)
A maternal effect is a causal influence of the maternal phenotype on the offspring phenotype over and above any direct effects of genes. There is abundant evidence that maternal effects can have a major impact on offspring fitness. Yet, no previous study has investigated the potential role of maternal effects in influencing the severity of inbreeding depression in the offspring. Inbreeding depression is a reduction in the fitness of inbred offspring relative to outbred offspring. Here, we tested whether maternal effects due to body size alter the magnitude of inbreeding depression in the burying beetle Nicrophorus vespilloides. We found that inbreeding depression in larval survival was more severe for offspring of large females than offspring of small females. This might be due to differences in how small and large females invest in an inbred brood because of their different prospects for future breeding opportunities. To our knowledge, this is the first evidence for a causal effect of the maternal phenotype on the severity of inbreeding depression in the offspring. In natural populations that are subject to inbreeding, maternal effects may drive variation in inbreeding depression and therefore contribute to variation in the strength and direction of selection for inbreeding avoidance.